The Effectiveness of Online Automatic Pension Determination in the Provincial Government of Bali (Research Study in the Personnel and Human Resources Development Agency Bali Province) - AA Krisna Harrysuta; Gede Wirata; Anak Agung Gde Raka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Determination of Automatic Retirement Online is a staffing service process in the form of electronic retirement determination by utilizing an employment service application system with few documents/paper or no documents/paper. This Automatic Pension Determination is a form of BKN commitment to the implementation of ASN staffing services that are integrated between the central government and local governments by cutting the flow of staffing services. The goal is to help the pension service process become faster, transparent and timely. However, the data on pensions for employees of the Provincial Government of Bali from 2018 to 2022 shows some ASN retirement certificates can not issued on time. This reseach determining effectiveness at online automatic retirement determination program for the ASN retirement process, especially at provincial governments of Bali. Qualitative descriptive research with inductive approachment is used. Data collection was carried out by interviewing a number of informants involved in online automatic retirement determination. Results showing implementation of online automatic pension determinations in the Bali provincial government has not been effective.